Marital Inequality and the Construction of a Sakinah, Mawaddah wa Rahmah Family: A Psychological and Quranic Perspective - Syamsiah Nur; Rama Dhini Permasari Johar; Belqis Nayla Shabihah (Jurnal Elsyakhshi, 2025)
This study examines how marriages marked by social and economic inequality can achieve the Islamic ideal of a sakinah, mawaddah wa rahmah family. It aims to identify key sources of conflict in unequal marriages and to formulate Quranic-based solutions for fostering marital harmony. Employing a qualitative approach, the study integrates psychological analysis with tafsir tahlili, utilizing bil ma’tsur and bil ma’qul methods through Tafsir al-Mishbah, Fi Zhilalil Quran, and Tafsir al-Maraghi. The findings reveal that disparities in financial conditions, occupational status, and social prestige constitute the primary sources of marital tension and emotional alienation. Nevertheless, harmony can be cultivated through mutual respect, balanced marital roles, and compassionate interaction grounded in Quranic principles, particularly those articulated in QS Ar-Rum [30]:21, QS Al-Hujurat [49]:10, 13, and QS At-Taubah [9]:71. This study contributes an integrative framework that combines psychological insights and Quranic interpretation to address marital inequality and strengthen Islamic family resilience.